Perovskite cell with iCVD micro-nano corrugated film and preparation method thereof

CN122892385APending Publication Date: 2026-10-09FUJIAN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611024223.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]然而,钙钛矿太阳能电池的入光侧通常包括玻璃等透明基底,当入射光照射至器件玻璃表面时,部分光会在空气/玻璃界面以及后续玻璃/介质界面发生反射,玻璃自身还会吸收部分透射光,导致实际到达钙钛矿吸光层的光强降低

Benefits of technology

本申请通过在ITO导电玻璃的玻璃外侧设置由引发式化学气相沉积形成的P(DVB-g-V3D3-g-PFDA)微纳褶皱薄膜,使入射光在微纳褶皱结构上发生多次反射,并利用微纳褶皱结构与空气之间的交错分布形成折射率梯度,从而缓解空气与薄膜之间因折射率突变产生的反射损失。由此,本申请能够提高入射光进入钙钛矿光伏功能层的比例,增强钙钛矿光伏功能层对光子的捕获和吸收利用,有利于提高短路电流密度和光电转换效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122892385A_ABST
    Figure CN122892385A_ABST
Patent Text Reader

Abstract

The application discloses a perovskite cell with an iCVD micro-nano corrugated film and a preparation method thereof, and relates to the technical field of light management of perovskite photovoltaic devices. The application aims to solve the problem of reflection loss of the ITO conductive glass on the light-incident side of the existing perovskite solar cell and the problem of the reduction of light intensity reaching the perovskite photovoltaic functional layer. The perovskite solar cell comprises ITO conductive glass and a perovskite photovoltaic functional layer arranged on the conductive side of the ITO conductive glass, and the outer side of the glass of the ITO conductive glass is provided with a P(DVB-g-V3D3-g-PFDA) micro-nano corrugated film formed by initiated chemical vapor deposition. The film comprises a PDVB film and PV3D3 and PPFDA films formed on the PDVB film, can guide incident light to reflect multiple times and form a refractive index gradient, so that the reflection loss on the light-incident side is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery material preparation technology, specifically to a perovskite battery with iCVD micro / nano wrinkled thin film and its preparation method. Background Technology

[0002] Perovskite solar cells have attracted widespread attention due to their high photoelectric conversion efficiency. To further improve the output performance of perovskite photovoltaic devices, light management techniques are commonly used to improve the transmission and utilization of incident light within the device. Anti-reflective coatings are a frequently used light management method; they can be applied to the light-incident surface of the device to regulate the propagation of light between air, glass, and the device's functional layers, allowing more incident light to enter the perovskite light-absorbing layer. Meanwhile, optical structures with specific surface morphologies have been used in the photovoltaic field to improve interfacial optical response, and anti-reflective and self-cleaning coatings are also considered effective directions for improving the utilization rate of incident light in photovoltaic devices.

[0003] However, the light-incident side of perovskite solar cells typically includes a transparent substrate such as glass. When incident light shines on the glass surface of the device, some light is reflected at the air / glass interface and the subsequent glass / dielectric interface. The glass itself also absorbs some transmitted light, resulting in a reduction in the actual light intensity reaching the perovskite absorber layer. Furthermore, absorption and scattering caused by surface contamination can also weaken the utilization of incident light and may affect material stability. Existing surface anti-reflection structures suitable for other photovoltaic systems are difficult to directly and effectively integrate onto the light-incident side surface of perovskite solar cells due to factors such as fabrication processes and device compatibility. Therefore, there is an urgent need for a light management solution that can reduce light-incident side reflection loss, improve the light-harvesting capability of the perovskite absorber layer, and is suitable for perovskite device fabrication conditions. Summary of the Invention

[0004] This application provides a perovskite solar cell with iCVD micro / nano wrinkled thin film and its preparation method. The technical problem to be solved by this application is that the ITO conductive glass on the light-incident side of the existing perovskite solar cell has reflection loss, which leads to a reduction in the intensity of incident light reaching the perovskite photovoltaic functional layer, thereby limiting the light absorption capacity and photoelectric conversion performance of the perovskite solar cell.

[0005] To achieve the above objectives, this application provides the following technical solution: In a first aspect, this application provides a perovskite solar cell with an iCVD micro / nano-wrinkled film, specifically a perovskite solar cell with an iCVD anti-reflection film, comprising an ITO conductive glass and a perovskite photovoltaic functional layer disposed on the conductive side of the ITO conductive glass. A P(DVB-g-V3D3-g-PFDA) micro / nano-wrinkled film formed by initiation chemical vapor deposition is disposed on the outer side of the ITO conductive glass. The P(DVB-g-V3D3-g-PFDA) micro / nano-wrinkled film includes a PDVB film deposited on the outer side of the glass and PV3D3 and PPFDA films further formed on the PDVB film. The P(DVB-g-V3D3-g-PFDA) micro / nano-wrinkled film has a micro / nano-wrinkled structure facing the incident light side, guiding the incident light to undergo multiple reflections on the micro / nano-wrinkled structure and forming a refractive index gradient, thereby reducing the reflection loss on the light-incident side of the ITO conductive glass.

[0006] Preferably, the PDVB film is a dense polyvinylbenzene film; the PV3D3 film is a poly(2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane) film; and the PPFDA film is a poly(1H,1H,2H,2H-perfluorodecyl acrylate) film.

[0007] Optionally, the bottom planar structure of the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film has a thickness of about 200 nm, a wrinkle height of 150–300 nm, and a wrinkle wavelength of about 500 nm.

[0008] Preferably, the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film contains PFDA, V3D3 and DVB components simultaneously.

[0009] Preferably, after the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is disposed on the outer side of the ITO conductive glass, the average transmittance of the ITO conductive glass in the range of 300–800 nm increases from 82.4% to 84.0%.

[0010] Preferably, after the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is disposed on the outer side of the ITO conductive glass, the average reflectivity of the ITO conductive glass in the range of 300–800 nm is reduced from 13.6% to 10.6%.

[0011] Preferably, the perovskite photovoltaic functional layer includes a NiOx thin film, a Me-4PACz layer, a FA0.85MA0.1Cs0.05PbI3 perovskite layer, a PEAI layer, a C60 layer, a BCP layer, and an Ag back electrode, which are sequentially disposed on the conductive side of the ITO conductive glass.

[0012] Preferably, the thickness of the C60 layer is 20 nm, the thickness of the BCP layer is 7 nm, and the thickness of the Ag back electrode is 100 nm.

[0013] Preferably, the PDVB film thickness is 20 nm - 1000 nm, the PV3D3 film thickness is 20 nm - 1000 nm, and the PPFDA deposition time is 1 min - 1 h.

[0014] Secondly, this application provides a method for preparing a perovskite solar cell, comprising the following steps: preparing a perovskite solar cell having an ITO conductive glass and a perovskite photovoltaic functional layer; wiping the outer side of the ITO conductive glass clean with ethanol; placing the ITO conductive glass face up into an initiation chemical vapor deposition reaction chamber; depositing a PDVB thin film on the outer side of the glass; and continuing to synthesize PV3D3 and PPFDA to obtain a P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled thin film.

[0015] Preferably, during the deposition of the PDVB film, the DVB monomer heating temperature is 45 °C and the flow rate is 0.82 sccm.

[0016] Preferably, when the laser curve shows that the thickness of the PDVB film reaches about 100 nm, the introduction of DVB monomer is stopped, and the synthesis of PV3D3 and PPFDA continues.

[0017] Thirdly, this application provides a perovskite solar cell with an iCVD micro / nano wrinkled film, specifically a perovskite solar cell with a target encapsulation structure, including an ITO conductive glass, a perovskite photovoltaic functional layer disposed on the ITO conductive glass, and an Ag electrode. A P(DVB-g-V3D3-g-PFDA) encapsulation film formed by initiation chemical vapor deposition is disposed on the side of the Ag electrode away from the perovskite photovoltaic functional layer. An ultraviolet-curable adhesive is disposed on the side of the P(DVB-g-V3D3-g-PFDA) encapsulation film away from the Ag electrode. A cover glass is disposed on the side of the ultraviolet-curable adhesive away from the P(DVB-g-V3D3-g-PFDA) encapsulation film.

[0018] Preferably, the P(DVB-g-V3D3-g-PFDA) encapsulation film is grown on the surface of the Ag electrode.

[0019] Preferably, the surface of the P(DVB-g-V3D3-g-PFDA) encapsulation film has a wrinkled structure.

[0020] Preferably, the P(DVB-g-V3D3-g-PFDA) encapsulation film includes a PDVB layer in direct contact with the underlying substrate, a PV3D3 layer mainly present in the middle of the film, and a PPFDA layer mainly present in the top of the film.

[0021] Preferably, the perovskite solar cell comprises, in sequence from the incident light direction, an ITO conductive glass, a NiOx hole transport layer, a Me-4PACz self-assembled layer, a FA0.85MA0.1Cs0.05PbI3 perovskite light-absorbing layer, a PEAI passivation layer, a C60 / BCP electron transport layer, a silver electrode, a P(DVB-g-V3D3-g-PFDA) encapsulation film, an ultraviolet-curable adhesive, and a cover glass.

[0022] Preferably, the P(DVB-g-V3D3-g-PFDA) encapsulation film is used as an intermediate buffer layer between the UV-curable adhesive and the device surface to reduce the adverse effects of the UV-curable adhesive on the perovskite solar cell.

[0023] Fourthly, this application provides a method for encapsulating a perovskite solar cell, comprising the following steps: after depositing C60 and BCP, the sample is removed from the vapor deposition machine, the functional layers around the sample are scraped off, and the central functional layer is retained to cover ITO; the sample is placed back into the vapor deposition machine for Ag electrode deposition; the prepared device is placed in the initiation chemical vapor deposition reaction chamber with the Ag electrode facing upward, and a P(DVB-g-V3D3-g-PFDA) encapsulation film is formed on the surface of the Ag electrode; a UV-curable adhesive is added to the surface of the P(DVB-g-V3D3-g-PFDA) encapsulation film, a cover glass is placed on top, and pressure is applied to cover the perovskite with the UV-curable adhesive; and the UV-curable adhesive is solidified by irradiation under a 365 nm UV lamp to obtain the Target encapsulation structure.

[0024] Preferably, during initiation chemical vapor deposition, when the laser curve shows that the PDVB thickness reaches about 1 μm, the DVB supply is stopped and V3D3 is turned on.

[0025] Preferably, V3D3 is stopped being introduced when the thickness of the PV3D3 interlayer reaches about 1 μm, and the PPFDA reaction is carried out.

[0026] Preferably, the PDVB film thickness is 100nm-20μm, the PV3D3 film thickness is 100nm-20μm, and the PPFDA deposition time is 1min-5h.

[0027] Preferably, 5 drops of UV-curable adhesive are added to the surface of the P(DVB-g-V3D3-g-PFDA) encapsulation film using a syringe, the cover glass is then placed on top, and pressure is applied to ensure that the cured adhesive completely covers the perovskite.

[0028] Fifthly, the application of an iCVD micro-nano wrinkled film in perovskite photovoltaic devices, wherein the iCVD micro-nano wrinkled film is a P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film, and the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is used for light management or encapsulation of perovskite solar cells.

[0029] When the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is used for light management of perovskite solar cells, the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is disposed on the outer side of the ITO conductive glass to guide incident light to undergo multiple reflections on the wrinkled structure of the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film and form a refractive index gradient. When the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is used for encapsulation of perovskite solar cells, the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is disposed on the side of the Ag electrode away from the perovskite photovoltaic functional layer, and together with the UV-curable adhesive and cover glass disposed on the side away from the Ag electrode, it forms a target encapsulation structure.

[0030] Compared with the prior art, this application has at least the following beneficial effects: This application utilizes a P(DVB-g-V3D3-g-PFDA) micro-nano-wrinkled thin film formed by initiation chemical vapor deposition on the outer surface of ITO conductive glass. This allows incident light to undergo multiple reflections on the micro-nano-wrinkled structure, and the staggered distribution of the micro-nano-wrinkled structure with air creates a refractive index gradient, thereby mitigating reflection losses caused by abrupt changes in refractive index between the air and the thin film. Consequently, this application can increase the proportion of incident light entering the perovskite photovoltaic functional layer, enhancing the perovskite photovoltaic functional layer's capture and absorption of photons, which is beneficial for improving short-circuit current density and photoelectric conversion efficiency.

[0031] Simultaneously, this application employs initiation-based chemical vapor deposition to form a micro / nano-wrinkled thin film on the outer surface of ITO conductive glass. This allows for the construction of surface light management films on top of the already fabricated perovskite solar cells, and the mechanical properties and thermal stability of the micro / nano-wrinkled film are improved through PDVB films. Test results show that after adding this micro / nano-wrinkled film, the average transmittance of the ITO conductive glass in the 300–800 nm range increases from 82.4% to 84.0%, while the average reflectance decreases from 13.6% to 10.6%. At the device level, the short-circuit current density of the perovskite solar cell increases from 23.73 mA / cm². 2 Increased to 24.35 mA / cm 2The photoelectric conversion efficiency was increased from 21.39% to 21.98%, and this micro-nano wrinkled film can effectively improve the light management effect of perovskite solar cells. Attached Figure Description

[0032] Figure 1 This is a schematic diagram of the anti-reflection mechanism of the wrinkled film; Figure 2 SEM images of the surface morphology and cross-section of P(DVB-g-V3D3-g-PFDA) wrinkled thin film; Figure 3 The FTIR spectrum of the P(DVB-g-V3D3-g-PFDA) wrinkled film; Figure 4 The transmittance and reflectance diagrams are for the original ITO glass and AR-ITO glass. Figure 5 The graph shows the change in transmittance of AR-ITO glass before and after ultraviolet light irradiation. Figure 6 The JV curves and EQE plots of the device before and after the deposition of the antireflective layer are shown. Figure 7 PL images of the perovskite film before and after deposition of the antireflective layer; Figure 8 Statistical graphs of PCE, JSC, VOC, and FF parameters for original devices and AR-PSC; Figure 9 This is a schematic diagram of the Target packaging process; Figure 10 SEM images of the surface and cross-section of a device encapsulated using iCVD thin-film packaging; Figure 11 SEM images and corresponding EDS images of the iCVD encapsulated thin film; Figure 12 FTIR spectrum of iCVD encapsulated thin film; Figure 13 Transmittance diagram of the iCVD encapsulation film; Figure 14 The contact angle of the iCVD encapsulation film changes over time. Figure 15 Images of perovskite films and iCVD films encapsulated in water during immersion tests. Figure 16 PLC (Power Linearity) versus JV (Jump V) curves of the perovskite film before and after iCVD packaging. Figure 17 Normalized PCE, JSC, VOC, and FF statistics for PSC before and after iCVD packaging; Figure 18 Images of thermal aging tests on the original perovskite film and the Target-encapsulated perovskite film. Figure 19 SEM images and absorption spectra of perovskite films with different encapsulation methods before and after thermal aging in air; Figure 20 XRD patterns of perovskite films with different encapsulation methods before and after thermal aging in air; Figure 21 The graph shows the change in conductivity of the functional layers before and after packaging using UVCA and Target packages. Figure 22 This is a schematic diagram of the device structure using a Target package; Figure 23 Electrochemical impedance spectroscopy (EIS) of devices using UVCA and Target packages; Figure 24 The EQE spectra of the device using Target packaging before and after packaging are shown. Figure 25 The graph shows the normalized PCE over time for original devices and target packaged devices at 25 °C and 65% RH in air. Figure 26 This is a maximum power point tracking plot of the original device and the target packaged device in air at 25 °C and approximately 30% RH. Detailed Implementation

[0033] To make the objectives, technical solutions, and advantages of this application clearer, the embodiments of this application will be described in detail below with reference to the accompanying drawings. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be arbitrarily combined with each other.

[0034] Many specific details are set forth in the following description in order to provide a full understanding of this application. However, this application may also be implemented in other ways different from those described herein. Therefore, the scope of protection of this application is not limited to the specific embodiments disclosed below.

[0035] The technical solution of this application will be further described below with reference to the accompanying drawings and embodiments. It should be understood that the following embodiments are only used to illustrate the technical solution of this application and are not intended to limit the scope of protection of this application.

[0036] Example 1: This embodiment provides a method for fabricating a perovskite solar cell, which includes an ITO conductive glass and a NiOx thin film, a Me-4PACz layer, a perovskite layer, a PEAI layer, a C60 layer, a BCP layer, and an Ag back electrode sequentially disposed on the conductive side of the ITO conductive glass.

[0037] First, a perovskite precursor solution of FA0.85MA0.1Cs0.05PbI3 was prepared. 0.21917 g FAI, 0.02384 g MAI, 0.01948 g CsI, and 0.69150 g PbI2 were weighed into a transparent glass bottle. To improve the perovskite crystal quality, an additional 0.00506 g MACl and 0.03457 g PbI2 were added. Then, 800 μL DMF and 200 μL DMSO were added to the transparent glass bottle, and the mixture was magnetically stirred at room temperature for 2 h in a glove box to obtain the perovskite precursor solution.

[0038] Then, perovskite solar cells were fabricated. ITO conductive glass was sequentially ultrasonically cleaned for 15 min each with deionized water and detergent, deionized water, acetone, and ethanol, respectively, followed by drying with a nitrogen gun. The cleaned ITO conductive glass was then subjected to ultraviolet ozone treatment for 30 min to remove surface contaminants and improve surface wettability.

[0039] 50 μL of a 6 mg / mL nickel oxide aqueous solution was dropped onto the surface of an ITO conductive glass treated with ultraviolet ozone, and then spin-coated at 4000 rpm for 30 s with an acceleration of 2000 rpm. The glass was then annealed in air at 100 °C for 10 min to form a NiOx thin film.

[0040] After transferring the sample to a glove box and allowing it to cool completely, 50 μL of a 0.5 mg / mL Me-4PACz isopropanol solution was dropped onto the NiOx film. The film was then spin-coated at 4000 rpm for 30 s with an acceleration of 4000 rpm, followed by annealing at 100 °C for 10 min to form the Me-4PACz layer.

[0041] 50 μL of filtered perovskite precursor solution was dropped onto the Me-4PACz layer. The mixture was first spin-coated at 1000 rpm for 10 s, and then at 5000 rpm for 40 s. When there were 5 s left in the second spin-coating, 150 μL of chlorobenzene was rapidly added to the wet perovskite film. After spin-coating, the sample was placed on a heating stage at 110 ℃ and annealed for 25 min to form a perovskite layer.

[0042] A PEAI isopropanol solution with a concentration of 1 mg / mL was dropped onto the perovskite layer, and the mixture was spin-coated at 4000 rpm for 30 s. After spin-coating, the mixture was annealed at 100 ℃ for 3 min to form a PEAI layer. The sample was then transferred to an evaporator, where 20 nm C60 and 7 nm BCP were deposited sequentially as electron transport layers, and finally 100 nm Ag was deposited as the back electrode to obtain a perovskite solar cell.

[0043] Example 2: In this embodiment, an iCVD antireflective film is formed on the outer side of the ITO conductive glass of the perovskite solar cell prepared in Example 1. Specifically, the outer side of the prepared perovskite solar cell's ITO conductive glass is wiped clean with ethanol, and then the ITO conductive glass is placed face up into the initiation chemical vapor deposition reaction chamber.

[0044] First, a PDVB thin film was deposited on the outer side of an ITO conductive glass. During deposition, the DVB monomer was heated to 45 °C and the flow rate was 0.82 sccm. When the laser curve showed that the PDVB film thickness reached approximately 100 nm, the DVB monomer flow was stopped, and 100 nm PV3D3 and 6 min PPFDA were synthesized to prepare a P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film.

[0045] Among them, PDVB film is a dense polyvinylbenzene film; PV3D3 film is a poly(2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane) film; and PPFDA film is a poly(1H,1H,2H,2H-perfluorodecyl acrylate) film.

[0046] The obtained P(DVB-g-V3D3-g-PFDA) micro-nano-wrinkled film is located on the outer side of the ITO conductive glass, and its surface forms a densely distributed and clearly defined micro-nano-wrinkled structure. This micro-nano-wrinkled structure faces the incident light side, allowing for the manipulation of the incident light, causing multiple reflections on the wrinkled structure. This prolongs the light propagation path within the wrinkled structure and reduces broadband reflection loss. Simultaneously, the staggered distribution of the micro-nano-wrinkled structure and air creates a refractive index gradient, mitigating reflection caused by abrupt changes in refractive index between the air and the film.

[0047] Morphological characterization of the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film revealed that the thickness of the bottom planar structure was approximately 200 nm, the wrinkle height was 150–300 nm, and the wrinkle wavelength was approximately 500 nm. Infrared spectroscopy of the film was performed, showing that at 1740 cm⁻¹... -1 1205cm -1 and 1150cm -1 A characteristic absorption peak belonging to PPFDA appears at 1018 cm⁻¹. -1 An absorption peak originating from Si-O-Si in PV3D3 appears at 2874 cm⁻¹. -1 and 2929cm -1 The presence of a characteristic absorption peak from PDVB indicates that the micro / nano wrinkled film contains PFDA, V3D3, and DVB components simultaneously.

[0048] To closely approximate the actual optical performance of this anti-reflective film when applied to perovskite solar cells, a P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film can be deposited on the outer surface of ITO conductive glass to form an AR-ITO glass. Test results show that the original ITO conductive glass has an average transmittance of 82.4% in the 300–800 nm range; after adding the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film, the average transmittance increases to 84.0%. The original ITO conductive glass has an average reflectance of 13.6% in the 300–800 nm range; after adding the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film, the average reflectance decreases to 10.6%.

[0049] Wrinkled structures have demonstrated excellent anti-reflection properties in crystalline silicon solar cells, but due to limitations in fabrication processes, their application in light management within perovskite photovoltaics is rarely studied. This application investigates their application in light management and integrates them onto the surface of perovskite solar cells. To improve the mechanical properties and thermal stability of the thin film, polydivinylbenzene (PDVB) films prepared by iCVD are introduced into the wrinkled films. The impact of the iCVD process on device performance is evaluated using current density-voltage characteristic curves, and the gain effect of the wrinkled films on the light absorption of the perovskite active layer is tested using external quantum efficiency and fluorescence spectroscopy. The results demonstrate that the wrinkled films prepared by iCVD are beneficial for the generation of photogenerated carriers, thereby optimizing the light absorption and photoelectric conversion efficiency of the perovskite solar cell.

[0050] Specifically, the fabrication of perovskite solar cells includes: (1) Preparation of perovskite precursor solution: for FA 0.85 MA 0.1 Cs 0.05 PbI3 precursor: 0.21917 g FAI, 0.02384 g MAI, 0.01948 g CsI, and 0.69150 g PbI2 were weighed into a transparent glass bottle. To improve the perovskite crystal quality, 0.00506 g MACl and 0.03457 g PbI2 were added additionally. Then, 800 μL of DMF and 200 μL of DMSO were added to the glass bottle, and the mixture was magnetically stirred at room temperature in a glove box for 2 h.

[0051] (2) Perovskite solar cell fabrication process: ITO conductive glass was ultrasonically cleaned for 15 min each time with deionized water and detergent, deionized water, acetone, and ethanol, respectively, and then dried with a nitrogen gun. The ITO glass was first treated with ultraviolet ozone for 30 min to remove surface contaminants and improve wettability. Then, 50 μL of 6 mg / mL nickel oxide (NiO) was pipetted into the glass. xAn aqueous solution of Me-4PACz was added dropwise to the ITO surface, and the mixture was spin-coated at 4000 rpm for 30 s with an acceleration of 2000 rpm. The mixture was then annealed in air at 100 °C for 10 min. The sample was transferred to a glove box and allowed to cool completely. Then, 50 μL of a 0.5 mg / mL Me-4PACz isopropanol solution was added dropwise to the NiO surface. x On the thin film, spin-coating was performed at 4000 rpm for 30 s with an acceleration of 4000 rpm. It was then annealed at 100 °C for 10 min. 50 μL of filtered perovskite precursor solution was added dropwise to the Me-4PACz layer, and spin-coated first at 1000 rpm for 10 s, then at 5000 rpm for 40 s. With 5 s remaining in the second spin-coating, 150 μL of chlorobenzene was rapidly added dropwise to the wet perovskite film. After spin-coating, the sample was annealed on a heating stage at 110 °C for 25 min. A 1 mg / mL PEAI isopropanol solution was added dropwise to the perovskite layer, and spin-coated at 4000 rpm for 30 s. After spin-coating, it was annealed at 100 °C for 3 min. The sample was then transferred to an evaporator to sequentially deposit 20 nm of C. 60 A 7 nm thick BCP was used as the electron transport layer, and finally a 100 nm Ag was deposited as the back electrode.

[0052] The preparation of iCVD antireflective films is as follows: The outer surface of the prepared perovskite solar cell ITO glass was carefully wiped clean with ethanol, and then placed face up into the iCVD reaction chamber. First, a PDVB thin film was deposited on the glass surface, with the DVB monomer heating temperature at 45 °C and a flow rate of 0.82 sccm. When the laser curve showed that the PDVB film thickness reached approximately 100 nm, the DVB monomer flow was stopped, and PV3D3 and PPFDA were synthesized to obtain P(DVB- g -V3D3- g -PFDA) film.

[0053] The characterization and testing are as follows: (1) Ultraviolet-vis absorption spectroscopy (UV-vis): The transmittance and reflectance of the thin film in the range of 300–800 nm were tested using UV-vis, and the reflectance was tested using an integrating sphere attachment. The thin film used for the test was deposited on unetched ITO conductive glass.

[0054] (2) Steady-state fluorescence spectrum (PL): The photoluminescence spectrum of the perovskite thin film was tested using PL. The excitation wavelength was 540 nm and the scanning speed was 240 nm / min.

[0055] (3) External quantum efficiency spectrum (EQE): The EQE spectrum and integrated current of the device before and after thin film deposition were tested in the range of 300–850 nm.

[0056] (4) Current density - voltage ( JV Characteristic curves: Using a solar simulator and digital source meter at AM 1.5 G (100 mW / cm²) 2 (Continue below) JV Curve testing was conducted, with an effective area of ​​0.05 cm². 2 .

[0057] To improve the mechanical properties and thermal stability of the thin film, enabling it to better withstand complex external environments and the heat generated during cell operation in perovskite solar cells, a dense layer of PDVB was first deposited on the ITO glass surface of the perovskite solar cell using iCVD. Subsequently, PV3D3 and PPFDA were sequentially deposited to obtain P(DVB- g -V3D3- g -PFDA) micro / nano-wrinkled films. PDVB, as a common dense cross-linked polymer, has demonstrated excellent mechanical properties in numerous studies, and remains stable even when heated to 300 °C. In this study, a micro / nano-wrinkled film with P(DVB- g -V3D3- g -PFDA) The perovskite solar cell with wrinkled thin film is called AR-PSC. Figure 1 The anti-reflection mechanism of the pleated structure is demonstrated. The pleated structure can effectively modulate incident light, guiding it to undergo multiple reflections, thereby extending the light propagation path within the pleated structure, effectively reducing reflection loss in the broadband band, and improving light absorption. Furthermore, the interlacing layers between the micro / nano pleated structure and the air create a gradient change in refractive index, effectively mitigating Fresnel reflection caused by abrupt changes in refractive index between the air and the thin film.

[0058] P(DVB- g -V3D3- g -PFDA) Surface and cross-sectional morphology of the thin film as follows Figure 2 As shown, specifically (a) surface morphology and (b) cross-sectional SEM images; the thin film forms densely distributed and clearly defined wrinkles on the silicon substrate surface, without defects or peeling areas. The thickness of the bottom planar structure of the thin film is approximately 200 nm, the wrinkle height is 150–300 nm, and the wrinkle wavelength is approximately 500 nm. The SEM results demonstrate that the introduction of PDVB did not affect the formation of the wrinkled structure.

[0059] P(DVB- g -V3D3- g The chemical composition of the PFDA-approved wrinkled film was tested using FTIR, and the results are as follows: Figure 3As shown. At 1740cm respectively. -1 1205cm -1 and 1150cm -1 Characteristic absorption peaks belonging to the carbonyl stretching vibration of PPFDA, as well as -CF2- and -CF3, were observed at 1018 cm⁻¹. -1 The absorption peak at 2874 cm⁻¹ originates from Si-O-Si in PV₃D₃. -1 and 2929cm -1 The peaks at these locations originate from the symmetric stretching vibration of CH3 and the asymmetric stretching vibration of -CH2- in PDVB, respectively. FTIR results demonstrate that the wrinkled film simultaneously contains PFDA, V3D3, and DVB components.

[0060] To closely approximate the actual anti-reflection effect of thin-film applications in perovskite solar cells, P(DVB-) was deposited on the outer side of an ITO conductive glass substrate. g -V3D3- g -PFDA) wrinkled film (AR-ITO glass). The transmittance of the conductive glass was tested using UV-vis, such as... Figure 4 As shown in Figure a, after depositing an anti-reflective film on the surface of ITO glass, the average transmittance increased from 82.4% to 84.0% in the 300–800 nm range, and the transmittance also improved in the visible light range of 400–800 nm. This broadband transmittance improvement is attributed to the unique wrinkled structure of the film. When incident light is reflected on the wrinkles, the reflected light may propagate to adjacent wrinkles and be absorbed and reused. Subsequently, the reflectivity of the ITO conductive glass was tested, as shown in Figure a. Figure 4 As shown in Figure b, compared to the original ITO glass, the AR-ITO glass exhibits lower reflectivity, with the average reflectivity in the 300–800 nm range decreasing from 13.6% of the original ITO glass to 10.6%, a reduction of 22%. The improvement in transmittance and reflectivity will promote the entry of sunlight into the perovskite layer, thereby contributing to the improvement of photocurrent and PCE.

[0061] Since perovskite solar cells need to operate continuously under sunlight, the resistance of the antireflective layer to ultraviolet light is of great importance. The ultraviolet stability of the film was tested under 365 nm ultraviolet light irradiation. The transmittance change of the ITO glass with the antireflective film is shown below. Figure 5 As shown, after 14 days of UV irradiation, the average light transmittance of the AR-ITO glass became 83.3%, a decrease of only 0.7% compared to the initial transmittance. Furthermore, the transmittance remained essentially unchanged in the visible light range, demonstrating excellent optical stability. Therefore, continuous operation under outdoor conditions will not easily compromise the anti-reflective properties of the film.

[0062] To test the impact of the anti-reflective film on device performance, and to ensure data comparability while eliminating fabrication differences and testing errors between different devices, this embodiment compares the photovoltaic characteristics of the same device at the same test point before and after the deposition of the anti-reflective layer. The results are as follows: Figure 6 As shown in Figure a, the AR-PSC short-circuit current density is significantly improved, from 23.73 mA / cm² in the original device. 2 Increased to 24.35 mA / cm 2 The corresponding PCE increased from 21.39% to 21.98% (Table 1). Meanwhile, the open-circuit voltage and fill factor remained almost unchanged before and after film deposition, indicating that the main factor for the improved PCE of the device was the increase in short-circuit current density. This is because the anti-reflection layer can effectively optimize the light management process, thereby enhancing the capture and absorption utilization rate of incident photons by the perovskite active layer.

[0063] Table 1. Changes in device performance parameters before and after wrinkled thin film deposition.

[0064] The external quantum efficiency (EQE) test results verified the above conclusions. The results show that the introduction of the antireflective layer improves the EQE across the wavelength range of 400–800 nm, reaching a peak of 92.48% at 475 nm. Figure 6 (b) This further demonstrates that the wrinkled film can suppress the reflection of incident light, allowing more photons to reach the perovskite absorbing layer. Correspondingly, the integrated current density of the AR-PSC is significantly improved, from 23.49 mA / cm² in the original device. 2 Increased to 24.14 mA / cm 2 Meanwhile, the increasing trend of EQE in the visible light band is highly consistent with the test results of the anti-reflective film transmittance. Since the other functional layers are consistent, it indicates that the increase in current density is mainly attributed to the anti-reflective layer enhancing the device's light-harvesting capability.

[0065] The enhanced absorption of incident light by the wrinkled film is also reflected in the PL spectrum. For example... Figure 7 As shown, compared with the control group, the perovskite film with the antireflective layer exhibits a higher photoluminescence (PL) intensity, indicating that the antireflective layer enhances the light absorption of the perovskite film, resulting in a higher photogenerated carrier density. Simultaneously, the PL peak position did not shift, indicating that the iCVD deposition process did not negatively affect the perovskite crystal structure.

[0066] To demonstrate the reproducibility of the results, statistical analysis of the relevant performance was conducted on devices fabricated from 14 different batches. The results are as follows: Figure 8 As shown, (a) PCE and (b) J of the original device and AR-PSC are shown. SC (c)V OC(d) FF parameter statistics.

[0067] Statistical results demonstrate that the anti-reflective layer significantly improves device efficiency and short-circuit current density. Devices with an anti-reflective layer exhibit an average short-circuit current density of 24.13 mA / cm². 2 ) and the maximum short-circuit current density (24.35 mA / cm) 2 Both are higher than the original device (23.56 mA / cm²). 2 and 23.81 mA / cm 2 The improvement effect of PCE and J SC Consistent with the previous results, the average PCE increased from 21.38% to 21.85%. Meanwhile, the open-circuit voltage and fill factor changed little before and after coating, verifying that the coating process does not affect battery performance.

[0068] This application applies iCVD wrinkled films to the conductive glass surface of perovskite solar cells, constructing a novel antireflective film. SEM images confirm that the PDVB layer used to improve film performance does not affect wrinkle formation. Incident light in P(DVB- g -V3D3- g The -PFDA) wrinkled film surface exhibits multiple reflections, and the staggered distribution of the film and air creates a refractive index gradient, effectively reducing light loss. The reflectivity decreases from 13.6% (ITO-glass) to 10.6% (AR-ITO glass). After 14 days of continuous UV irradiation, the film transmittance only decreased by 0.7%, demonstrating the stable anti-reflective effect of the wrinkled film under outdoor conditions. The enhanced fluorescence spectrum indicates that the anti-reflective layer deposition does not damage the perovskite material, and the light absorption of the active layer is enhanced. EQE and JV Tests confirmed this result; with the anti-reflective layer, the short-circuit current density of the device increased by 0.62 mA / cm². 2 The PCE increased from 21.39% to 21.98%, and the statistical results proved the reproducibility of the method.

[0069] In this application, iCVD is used to deposit a micro-nano wrinkled thin film on the surface of the silver electrode of a perovskite solar cell. This film serves as an intermediate buffer layer between the UVCA and the device for device encapsulation, improving its stability. Unlike technologies such as PECVD or ALD, iCVD does not involve plasma or high temperatures during the deposition process, thus avoiding degradation of the perovskite layer or charge transport layer. Therefore, JVThe curve results show that the device efficiency remains essentially unchanged before and after iCVD coating, and PL spectroscopy verifies that the iCVD process does not damage the perovskite. The perovskite film encapsulated with the wrinkled film exhibits excellent stability in water. By comparing the morphology, absorption spectrum, X-ray diffraction, and electrical properties of the perovskite film before and after aging, it was found that the iCVD wrinkled film can effectively reduce the adverse effects of UVCA and delay perovskite degradation. Under the combined effect of the iCVD wrinkled film and UVCA, the encapsulated device can maintain a longer operating life under high humidity and continuous illumination than the unencapsulated device and the device encapsulated by UVCA alone.

[0070] Example 3: Device performance with iCVD antireflective film This embodiment tests the performance of a perovskite solar cell with an iCVD antireflective film. To ensure data comparability, the same test point of the same perovskite solar cell was selected to compare its photovoltaic performance before and after the deposition of the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film. The perovskite solar cell with the deposited P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is designated as AR-PSC.

[0071] Preferably, the PDVB film thickness is 20nm-1000nm, the PV3D3 film thickness is 20nm-1000nm, and the PPFDA deposition time is 1min-1h.

[0072] At AM 1.5 G, 100 mW / cm 2 The JV characteristic curve was tested under illumination conditions, with an effective device area of ​​0.05 cm². 2 Test results show that the short-circuit current density of the original device is 23.73 mA / cm². 2 The open-circuit voltage was 1.106 V, the fill factor was 81.48%, and the photoelectric conversion efficiency was 21.39%. After depositing P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled films, the short-circuit current density of AR-PSC increased to 24.35 mA / cm². 2 The open-circuit voltage was 1.108 V, the fill factor was 81.46%, and the photoelectric conversion efficiency was increased to 21.98%. This shows that the improvement in the photoelectric conversion efficiency of the device after adding the anti-reflective film mainly comes from the increase in short-circuit current density.

[0073] The external quantum efficiency (EQE) of the device was further tested in the wavelength range of 300–850 nm. The results showed that after introducing the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film, the EQE of the device was improved in the wavelength range of 400–800 nm, reaching a peak of 92.48% at 475 nm. Correspondingly, the integrated current density of the device increased from 23.49 mA / cm² in the original device. 2 Increased to 24.14 mA / cm 2 This result demonstrates that micro- and nano-wrinkled films can suppress incident light reflection, allowing more photons to reach the perovskite light-absorbing layer.

[0074] Steady-state fluorescence spectroscopy (PL) was performed on the perovskite thin film at an excitation wavelength of 540 nm and a scan rate of 240 nm / min. The results showed that, compared to the control group without an anti-reflective film, the perovskite thin film with the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film exhibited a higher PL intensity, indicating that the anti-reflective film improved the light absorption of the perovskite film and increased the photogenerated carrier density. Simultaneously, the PL peak position did not shift, indicating that the initiation-based chemical vapor deposition process did not negatively affect the perovskite crystal structure.

[0075] To verify the reproducibility of the results, statistical analysis was performed on devices fabricated from 14 different batches. The results showed that the average short-circuit current density of the device with the anti-reflective film was 24.13 mA / cm². 2 The maximum short-circuit current density is 24.35 mA / cm². 2 All of these are higher than the average short-circuit current density of 23.56 mA / cm² of the original device. 2 And the maximum short-circuit current density is 23.81 mA / cm². 2 The average photoelectric conversion efficiency of the device with the anti-reflective film increased from 21.38% to 21.85% compared to the original device. The open-circuit voltage and fill factor changed little before and after the deposition of the anti-reflective film, indicating that the deposition process of the anti-reflective film had little impact on the original electrical performance of the device.

[0076] Example 4: This embodiment provides a perovskite solar cell with a Target encapsulation structure and its encapsulation method. The perovskite solar cell, from the direction of incident light, comprises, in sequence, ITO conductive glass, a NiOx hole transport layer, a Me-4PACz self-assembled layer, a FA0.85MA0.1Cs0.05PbI3 perovskite light-absorbing layer, a PEAI passivation layer, a C60 / BCP electron transport layer, a silver electrode, a P(DVB-g-V3D3-g-PFDA) encapsulation film, a UV-curable adhesive, and a cover glass.

[0077] Before encapsulation, a perovskite solar cell with ITO conductive glass, a perovskite photovoltaic functional layer, and a silver electrode was fabricated. To facilitate testing after encapsulation, after depositing C60 and BCP, the sample was removed from the vapor deposition machine, and the functional layers around the sample were scraped off with a scriber inside a glove box, leaving sufficient functional layers in the center to cover the ITO and ensure the active area remained unchanged. The sample was then placed back into the vapor deposition machine for Ag electrode deposition.

[0078] After the Ag electrode is deposited, the prepared device is placed in the initiation chemical vapor deposition (ICV) chamber with the Ag electrode facing upwards. Copper strips are placed on both sides as masks to prevent polymer deposition on the Ag electrode test sites during subsequent iCVD deposition. All functional layers below the copper strips, except for the silver electrode, are scraped off, and the masked silver electrode serves as the test site for subsequent JV curves.

[0079] During the iCVD deposition process, DVB was stopped when the PDVB thickness reached approximately 1 μm as indicated by the laser curve, and V3D3 was activated. Similarly, V3D3 was stopped when the PV3D3 interlayer thickness reached approximately 1 μm, and the PPFDA reaction commenced. Because the PPFDA deposition process generates wrinkles and scattering, the laser curve could not accurately reflect the film information. Therefore, the reaction was stopped after 35 minutes of PFDA monomer introduction. This resulted in the formation of a P(DVB-g-V3D3-g-PFDA) encapsulation film on the Ag electrode surface.

[0080] Subsequently, 5 drops of UV-curable adhesive were added to the surface of the P(DVB-g-V3D3-g-PFDA) encapsulation film using a syringe, the cover glass was placed on top, and pressure was applied to ensure that the UV-curable adhesive completely covered the perovskite region; finally, the adhesive was irradiated under a 365 nm UV lamp to solidify, resulting in the Target encapsulation structure.

[0081] The resulting P(DVB-g-V3D3-g-PFDA) encapsulation film was grown on the surface of the silver electrode, exhibiting a wrinkled structure. The cross-sectional structure revealed ITO, perovskite crystals, the silver electrode, and the encapsulation film, which was positioned between the silver electrode and the UV-curable adhesive. This structure allows the P(DVB-g-V3D3-g-PFDA) encapsulation film to act as an intermediate buffer layer between the UV-curable adhesive and the device surface, reducing the adverse effects of the UV-curable adhesive on the perovskite solar cell.

[0082] Example 5: This embodiment tests the stability and packaging compatibility of the Target packaged device obtained in Embodiment 4.

[0083] First, steady-state fluorescence spectroscopy was performed on the perovskite thin film before and after the iCVD encapsulation process. The results showed that the position and intensity of the PL peak remained basically unchanged after the iCVD polymer was deposited on the perovskite thin film, indicating that no significant lattice change or decomposition occurred in the perovskite layer, and the iCVD process did not introduce significant additional defects to the perovskite surface and grain boundaries.

[0084] JV testing was further performed on the inverting device based on the ITO / NiOx / Me-4PACz / FA0.85MA0.1Cs0.05PbI3 / PEAl / C60 / BCP / Ag structure at the same test point before and after iCVD deposition. The test results showed that the short-circuit current density of the device before iCVD deposition was 23.71 mA / cm². 2 The open-circuit voltage is 1.120 V, the fill factor is 82.99%, and the photoelectric conversion efficiency is 22.05%. After iCVD deposition, the short-circuit current density of the device is 23.60 mA / cm². 2 The open-circuit voltage was 1.125 V, the fill factor was 81.46%, the photoelectric conversion efficiency was 21.63%, and the initial efficiency was maintained at 98.1%. These results indicate that the iCVD packaging process has a relatively small impact on the photovoltaic performance of the device.

[0085] Conductivity tests were performed on the functional layers using UVCA and Target packages before and after packaging. The test results show that the conductivity of the UVCA-packaged sample decreased from 3.25 × 10⁻⁶ before packaging. -6 S / cm becomes 4.86×10 after packaging. -6 S / cm; The conductivity of the target packaged sample increased from 3.48 × 10⁻⁶ before packaging. -6 S / cm becomes 3.73×10 after packaging. -6 S / cm. This result indicates that introducing a P(DVB-g-V3D3-g-PFDA) encapsulation film between the UV-curable adhesive and the device surface can reduce the change in the conductivity of the functional layer before and after encapsulation.

[0086] Electrochemical impedance spectroscopy (EIS) tests were performed on devices using UVCA and Target encapsulation, and fitting analysis was conducted. In the UVCA-encapsulated device, the series resistance RS was 17.1 Ω and the charge transport resistance Rct was 742.8 Ω before encapsulation; after UVCA encapsulation, the series resistance RS was 11.9 Ω and the charge transport resistance Rct was 1422.9 Ω. In the Target-encapsulated device, the series resistance RS was 22.2 Ω and the charge transport resistance Rct was 966.8 Ω before encapsulation; after depositing the polymer encapsulation film, the series resistance RS was 22.1 Ω and the charge transport resistance Rct was 972.1 Ω; after forming the Target package, the series resistance RS was 13.2 Ω and the charge transport resistance Rct was 1089.2 Ω. These results indicate that the P(DVB-g-V3D3-g-PFDA) encapsulation film can alleviate the problem of increased charge transport resistance caused by UVCA encapsulation alone.

[0087] To evaluate the impact of target packaging on the spectral response of the device, the EQE spectra of the unpackaged device and the target-packaged device were compared. The results showed that the EQE spectra of the devices before and after packaging were essentially the same, with no significant decrease in the 300–850 nm wavelength range. The integrated current density increased from 23.49 mA / cm² before packaging. 2 The packaged value is 23.42 mA / cm. 2 This indicates that the Target package did not cause significant damage to the device's light absorption.

[0088] Further humidity stability testing was conducted on the Target packaged devices. The packaged devices were aged in a constant temperature and humidity environment of 25 °C and 65% RH. The JV curve of the devices was measured at regular intervals, and the measured data were normalized. The test results showed that the unpackaged devices maintained only 75% of their initial efficiency after 48 hours of aging, and the PCE decreased to 29% of the initial efficiency after 552 hours of aging. The devices using the Target package maintained 80% of their initial efficiency after 1350 hours of continuous aging at 65% RH.

[0089] Subsequently, maximum power point tracking (MPPT) tests were conducted in an air environment of 25 °C and approximately 30% RH, using an LED lamp with an equivalent luminous intensity of 1 sun. The test results showed that the efficiency of the unpackaged raw device rapidly declined, reaching less than 40% of the initial PCE after 100 hours; the Target-packaged device maintained 70% of its initial efficiency after 500 hours of continuous operation. These results indicate that Target packaging is beneficial for improving the stability of perovskite solar cells under humid conditions and continuous illumination.

[0090] Although the efficiency of perovskite solar cells is currently very close to that of commercial crystalline silicon cells, effective light management strategies are essential to surpass silicon cells and fabricate higher-efficiency perovskite photovoltaic devices. When incident light shines on the glass surface of the device, 4% of the incident light is reflected, 1% of the transmitted light is absorbed by the glass, and another 4% of the light is reflected at the second glass and dielectric surface, ultimately leaving only 91% of the light passing through the glass. Furthermore, due to surface contamination, absorption and scattering caused by dirt further affect the light intensity incident on the perovskite active layer and may accelerate material degradation. Anti-reflection (AR) self-cleaning coatings offer a highly attractive solution to these problems.

[0091] The encapsulation process for perovskite solar cells is as follows: To facilitate testing after packaging, C is deposited... 60 After BCP, the sample is removed from the vapor deposition machine. Inside the glove box, each functional layer around the sample is carefully scraped off with a scriber, leaving sufficient functional layer in the center to cover the ITO and maintain the active area. The sample is then placed back into the vapor deposition machine for Ag electrode deposition. The prepared device is placed in the iCVD reaction chamber with the Ag electrode facing upwards, and copper strips are placed on both sides as masks to prevent polymer deposition on the Ag electrode during subsequent iCVD deposition. All functional layers below the copper strips, except for the silver electrode, are scraped off; the covered silver layer is for subsequent deposition. JV The curve provides the test sites.

[0092] Since the thickness of the encapsulation material affects barrier performance, the thickness of each layer of the iCVD film was modified to improve the protective capability of the film. During the iCVD deposition process, when the laser curve showed that the PDVB thickness reached approximately 1 μm, DVB was stopped, and V3D3 was activated. When the thickness of the PV3D3 intermediate layer reached approximately 1 μm, V3D3 was stopped, and the PPFDA reaction proceeded. Because the PPFDA deposition process resulted in wrinkles causing scattering, the laser curve could not accurately reflect the film information; therefore, the reaction was stopped after 35 minutes of PFDA monomer introduction. Five drops of UV-curable adhesive were added to the iCVD film surface using a syringe, a cover glass was placed on top, and appropriate pressure was applied to ensure the adhesive completely covered the perovskite. Finally, the adhesive was cured under a 365 nm UV lamp. In this study, the above encapsulation method is referred to as Target encapsulation. The specific encapsulation process is as follows: Figure 9 As shown.

[0093] For the control group using only UVCA encapsulation, the same method was used, where the functional layers around the perimeter were scraped off. After electrode deposition, five drops of UV-curable adhesive were added directly to the electrode surface, and a cover glass was placed on top. Finally, the device was cured under a UV lamp.

[0094] The characterization and testing are as follows: (1) XRD test: A perovskite film was prepared on a quartz substrate. The encapsulated perovskite film was exposed by peeling off the UV-cured adhesive and XRD test was performed at 40 kV and 40 mA.

[0095] (2) Conductivity test: C is deposited on ITO glass. 60 After BCP, the surrounding functional layer is scraped off, a silver electrode is deposited, and iCVD coating is performed. JV The curve testing system tests the current-voltage curve at 0.5 V.

[0096] (3) Electrochemical impedance spectroscopy (EIS): 0.1–10 μV were measured at a bias voltage of 1 V. 5 The impedance spectrum of the packaged device in the Hz range was obtained, and the data was fitted using ZView software.

[0097] (4) Stability test: The packaged device is placed in a constant temperature and humidity chamber, with the temperature controlled at 25 ℃ and the relative humidity (RH) controlled at 65%. The packaged device is tested at regular intervals. JV Curves were used to evaluate humidity stability; maximum power point (MPP) tracking tests were employed to continuously track the operational stability of the packaged device under equivalent sunlight in air.

[0098] Figure 10 SEM images of the iCVD encapsulation film deposited on perovskite solar cells are shown. (P(DVB-)) g -V3D3- g The surface of the PFDA-encapsulated film exhibits a distinct wrinkled structure. In the cross-sectional view, the bottom ITO, perovskite crystals, silver electrode, and encapsulated film are clearly visible. Other functional layers are difficult to distinguish due to their small thickness, with the encapsulated film growing in close contact with the electrode surface.

[0099] P(DVB- g -V3D3- g The layered structure of the PFDA-encapsulated thin film can be demonstrated through elemental distribution, such as the EDS of the thin film deposited on the silicon wafer. Figure 11 The silicon (Si) element originates from the bottom silicon wafer and the V3D3 intermediate layer. The carbon (C) element is distributed throughout the film, forming a clear boundary between the film and the bottom silicon wafer. Combined with the Si element distribution map, this demonstrates that PV3D3 is primarily located in the middle of the film. The sulfur (F) element is mainly present at the top of the film, corresponding to PPFDA. The combined distribution of these three elements proves that the material in direct contact with the silicon wafer is PDVB, which does not contain Si or F.

[0100] FTIR spectra confirmed P(DVB- g -V3D3- gThe successful synthesis of PFDA-approved thin films, such as Figure 12 As shown. The chemical composition of the iCVD encapsulation film is the same as that of the antireflective film, with only differences in thickness and surface morphology. Therefore, the FTIR of the encapsulation film will not be described in detail.

[0101] Although the encapsulation film is not the first part of the device structure that incident light comes into contact with, high visible light transmittance remains a requirement for ideal encapsulation materials. High transmittance is especially essential for transparent solar cells used in applications such as tandem cells or building-integrated photovoltaics (BIPV). Figure 13 The results show the transmittance of ITO glass with an encapsulation film. In the 300–800 nm range, its average transmittance is 82.6%, 0.2% higher than the original ITO glass. This indicates that the encapsulation material does not affect visible light transmission and is compatible with high-efficiency photovoltaic devices. Compared to the significant increase in transmittance of the anti-reflection layer, the anti-reflection effect of the encapsulation film is weak. This may be due to the change in morphology causing the incident light to not be effectively reflected multiple times. The slight increase in transmittance originates from the gradient change in refractive index.

[0102] Hydrophobicity is an important criterion for evaluating the effect of thin film encapsulation. The relationship between the contact angle of the thin film and time was tested using a contact angle measuring instrument. Figure 14 After 20 seconds of contact between the water droplet and the film, the contact angle was 139.0°, which decreased slightly to 138.4° after 1 minute, and further decreased to 134.4° after 5 minutes. The encapsulation film exhibited weaker hydrophobicity than the antireflective film, possibly due to its larger contact area with the water droplet. According to the Cassie-Baxter wetting model, the contact angle of the liquid on a composite surface composed of two materials (…) θ ) can be represented as: cos θ = f 1cos θ 1+ f 2cos θ 2(1) in f 1 and f 2 represents the area fraction of the total surface area for each of the two materials. f 1 and f The sum of 2 is 1. θ 1 and θ 2 represents the intrinsic contact angle of the droplet on the two materials. The wetting of a water droplet on a wrinkled surface can be considered as a three-phase contact consisting of the solid surface, the water droplet, and the air trapped between the wrinkles. The contact angle of water in the air layer is approximately 180°, i.e., cos... θ 2 is -1, therefore equation (1) can be simplified to: cos θ = f (cos θ + 1)-1(2) in f Represents the area fraction of the contact between the solid and the water droplet. θ Let be the intrinsic contact angle of water on a solid. Therefore, reducing the contact area between the solid and the liquid is beneficial for increasing the contact angle. The wrinkled structure of the antireflective film has a higher aspect ratio and a smaller solid-liquid contact area, which is beneficial for forming a stable Cassie state. The encapsulation film is closer to a plane and has a larger solid-liquid contact area. According to equation (2), its contact angle will decrease.

[0103] Achieving excellent encapsulation results requires that the encapsulation process does not damage the perovskite material. Therefore, this study investigated the impact of the iCVD process on the performance of the perovskite film and the device. First, a perovskite film was spin-coated onto ITO glass. After iCVD deposition, the perovskite film maintained a black phase, indicating that the low-temperature deposition conditions did not cause degradation of the perovskite material. The original perovskite film and the encapsulated perovskite film were immersed in water to compare the color change rate of the perovskite film. Optical photographs are shown below. Figure 15 As shown, the perovskite film without iCVD encapsulation degrades rapidly after immersion in water, changing from a photoactive black phase to an inactive yellow phase in just 10 seconds. In contrast, the perovskite film encapsulated with iCVD retains its original black phase even after being fully immersed in water for half an hour, demonstrating excellent barrier properties against liquid water.

[0104] The steady-state fluorescence spectra of the perovskite films before and after encapsulation were then compared. For example... Figure 16 As shown in Figure a, the PL peak position is related to the band gap of the material. Strain introduced by the encapsulation material may cause changes in the perovskite band gap, resulting in peak position shift. Furthermore, phase transitions and the wide-bandgap PbI2 exfoliated during degradation also affect the PL peak position. The PL intensity reflects the radiative recombination efficiency in the perovskite; increased defects leading to enhanced non-radiative recombination result in a decrease in PL peak intensity. After depositing iCVD polymers on the perovskite film, the PL peak position and intensity remained essentially unchanged, indicating that the perovskite layer did not undergo lattice changes or decomposition. The iCVD process did not introduce strain, preserving the perovskite's band gap structure. The encapsulation film exhibits good chemical compatibility with the perovskite layer, the encapsulation process did not introduce additional defects to the perovskite surface or grain boundaries, and non-radiative recombination was not enhanced.

[0105] Finally, to investigate the impact of the iCVD packaging process on device performance, tests were conducted on devices based on ITO / NiO. x / Me-4PACz / FA 0.85 MA 0.1 Cs 0.05 PbI3 / PEAI / C60 / BCP / Ag structure inverse device at the same test point before and after iCVD coating JV Characteristic curves. For example... Figure 16 As shown in Table 2, before and after iCVD deposition, the changes in various performance parameters of the device are minimal. SC From 23.71 mA / cm 2 Slightly decreased to 23.60 mA / cm 2 V OC The voltage was increased from 1.120 V to 1.125 V, the FF decreased from 82.99% to 81.46%, and the PCE decreased from 22.05% to 21.63%, while maintaining the initial efficiency of 98.1%. The iCVD packaging process has little impact on device performance.

[0106] Table 2 Performance parameters of perovskite solar cells before and after iCVD encapsulation

[0107] To prove that the results were not accidental, the normalized photovoltaic performance parameters of 10 different devices at the same test point before and after iCVD coating were statistically analyzed, such as... Figure 17 As shown, after iCVD packaging, the average PCE of the device remains at 97.5% of the initial efficiency. SC Almost unchanged, V OC On average, it increased by 1.5%, while FF decreased relatively more, but it still maintained the original 96.3%.

[0108] To achieve better encapsulation, a UV-curable adhesive was introduced after iCVD coating, and UV-curable adhesive (UVCA) was used to bond the iCVD encapsulation film to the cover glass, a process termed Target Encapsulation. The protective capability of Target Encapsulation against perovskite was systematically evaluated by accelerating the aging of the perovskite film in air at 85 °C. To visually characterize the actual protective effect of Target Encapsulation, the morphological evolution of samples at different aging stages was recorded, and optical photographs are shown below. Figure 18As shown in the figure, after one day of heat aging, the edge area of ​​the unencapsulated film turned dark brown first, indicating that the film had begun to degrade. After four days, the perovskite film changed from black to brown. After 10 days of continuous heat aging, the film turned completely yellow with a slight whitening, indicating that the perovskite was close to complete degradation. In stark contrast, no color change was observed in the perovskite film encapsulated with Target after 1 and 4 days of aging. Even after 10 days of continuous heating in air, the perovskite maintained its initial black phase, demonstrating significantly better stability than the unencapsulated perovskite. These results indicate that Target encapsulation can provide excellent protection and significantly inhibit air- and heat-induced perovskite degradation. Literature indicates that hermetically sealed encapsulation can suppress the volatilization of gaseous degradation products, such as I2, HI, CH3NH2, and other substances that are easily sublimated or have low boiling points. This increases the concentration of degradation products within the closed system, which is beneficial for the reaction to reach dynamic equilibrium, thereby inhibiting perovskite decomposition.

[0109] Although optical photographs demonstrate that Target encapsulation significantly improves the stability of perovskites, morphological characterization alone cannot distinguish the individual contributions of UVCA and iCVD films in the encapsulation system, nor can it rule out the possibility that this improvement effect is primarily attributable to UVCA. To better analyze the role of the iCVD polymer and eliminate the influence of the UV-curable adhesive, this study included a control group, in which UVCA was directly used to bond the cover glass for encapsulation without introducing the iCVD polymer.

[0110] The microstructure evolution of perovskite films before and after thermal aging under different encapsulation strategies was investigated. Figure 19Figure a shows a SEM image of the buried interface obtained by UV-curing adhesive peeling. Before aging, all perovskite buried interfaces exhibited a dense, continuous, and well-defined crystal structure with smooth surfaces and no lead iodide. After one week of heating and aging in air, the morphology of the unencapsulated perovskite film changed significantly, with many loose porous structures appearing on the surface and a significant increase in roughness. This structure has been reported in previous literature. Since the thermal aging process was carried out indoors, the perovskite film may have been affected by factors such as heat, moisture, and light. The appearance of this porous structure may be due to the reduced activation energy of ion migration and perovskite degradation under external influences, leading to the formation of PbI2 and the generation of volatile gases (such as NH3, HI, I2, etc.). These gases can escape freely, resulting in the appearance of vacancies and interstitials. For perovskites encapsulated with UVCA, the curing adhesive completely covers the perovskite surface to form an airtight seal, effectively preventing the escape of volatile gases generated during degradation, thereby inhibiting further degradation of the perovskite. The perovskite film encapsulated in this way retains some crystalline structure after aging, but it has a high number of pinholes and needle-like PbI2 crystals, which may be related to the interaction between the cured adhesive and the perovskite, thus limiting its protective effect. In contrast, the perovskite film encapsulated with Target exhibits excellent stability, with degradation significantly suppressed. SEM images show that the perovskite film basically maintains its original crystalline structure, with almost no PbI2 observed. The few pinholes appearing in the images are likely due to the escape of gases such as NH3. Nevertheless, Target encapsulation, using iCVD polymer as the intermediate layer between the device and UVCA, still demonstrates a stronger protective effect than UVCA encapsulation alone, greatly suppressing the release of decomposition products and the degradation reaction.

[0111] Figure 19 (a) SEM images and (b) absorption spectra of perovskite films with different encapsulation methods before and after thermal aging in air; the optical stability of perovskite films under different encapsulation strategies before and after aging was studied by comparing UV-Vis absorption spectroscopy. Figure 19(b) Perovskite films using different encapsulation strategies all exhibited typical perovskite light absorption characteristics before aging, showing a clear absorption edge around 800 nm. After 2 days of aging, the absorbance of unencapsulated perovskite decreased significantly. After 14 days of continuous aging, the absorption edge around 800 nm of the unencapsulated film completely disappeared, indicating significant degradation of the perovskite. Perovskite encapsulated with UVCA showed only a slight decrease in absorbance in the 500–700 nm wavelength range after 2 days of aging, and the absorbance change was not significant after 14 days, with a much smaller decrease than that of unencapsulated perovskite. Perovskite encapsulated with Target showed only a slight change in absorbance in the 500–600 nm range after 2 days of aging, and the decrease in absorbance after 14 days of continuous aging was significantly smaller than that of UVCA encapsulated perovskite. Furthermore, the absorption edge of the Target-encapsulated perovskite near 800 nm did not change significantly during aging, indicating that the Target-encapsulated perovskite film retained its initial optical properties. The encapsulation protection effect was better than that of single UVCA encapsulation, demonstrating good stability.

[0112] The compositional changes of the perovskite film before and after aging were tested using XRD. In this embodiment, a perovskite film was prepared on a quartz substrate. To maintain consistency with the SEM test samples, the perovskite buried interface was exposed by UV-curing adhesive. Figure 20 These are the XRD patterns of three perovskite films after undergoing the same aging conditions. Before aging, the perovskite film exhibits distinct characteristic diffraction peaks corresponding to the (100) crystal plane of perovskite. After one week of heating and aging in air, for the unencapsulated perovskite film, the (100) characteristic peak of perovskite almost completely disappeared, and a distinct PbI2 diffraction peak appeared at 2θ=12.7°. This indicates that the unencapsulated perovskite underwent almost complete phase decomposition, and the crystal structure of the photoactive phase was completely destroyed, corroborating the aforementioned result of complete microstructural collapse in SEM characterization. Although the perovskite film encapsulated with UV-curable adhesive retained all characteristic diffraction peaks, a distinct PbI2 peak appeared, proving that this encapsulation method cannot effectively prevent perovskite degradation. Furthermore, a significant shift in the PbI2 peak position was observed compared to the PbI2 peak position observed after aging of the unencapsulated perovskite, corresponding to the different morphologies of PbI2 crystals observed in the SEM images. The perovskite film encapsulated by Target retained all characteristic peaks while only showing a weak PbI2 peak, indicating that introducing iCVD film encapsulation on top of the cured adhesive provides more comprehensive protection for the stability of the perovskite film.

[0113] To evaluate the impact of encapsulation materials on the electrical performance of the device and further explore the role of iCVD polymers, this embodiment tested the electron transport layer (C) by measuring its conductivity. 60Charge transport at the interface between the BCP and the silver electrode results are as follows: Figure 21 As shown. The conductivity is calculated according to equation (3): σ=d / (AR) (3) in σ For electrical conductivity, d Represents the thickness of the functional layer. A Represents the active area. R For resistance. In the calculations, the thickness of the electron transport layer is set to 27 nm for vapor deposition, and the active area is 0.075 cm². 2 The resistance is obtained through linear fitting. Figure 21 The data was obtained from [the data source]. Table 3 shows the calculated conductivity data. From [the data source]... Figure 21 As can be seen, different packaging strategies have different effects on the functional layer. The conductivity of the functional layer using UVCA packaging changes significantly before and after packaging, from the initial 3.25 × 10⁻⁶. -6 S / cm increased to 4.86×10 -6 The conductivity increased by 49.5% (S / cm), which is likely due to the penetration behavior of UVCA. Conversely, the functional layer using Target packaging showed less change in conductivity before and after packaging, from 3.48 × 10⁻⁶ before packaging. -6 S / cm increased slightly to 3.73×10 -6 The increase in S / cm was 7.2%, indicating that the presence of iCVD polymer can mitigate the impact of UVCA on the device, help maintain the original performance, and demonstrate good packaging compatibility.

[0114] Table 3. Conductivity of functional layers before and after using UVCA and Target packages

[0115] Since the encapsulation layer protects the complete device in practical applications, this embodiment implements target encapsulation on the complete perovskite photovoltaic device to more comprehensively illustrate the effect of target encapsulation. Figure 22 This is a schematic diagram of the packaged device. From bottom to top along the incident light direction, the layers are ITO conductive glass, NiO, etc. x Hole transport layer, Me-4PACz self-assembly layer, FA 0.85 MA 0.1 Cs 0.05 PbI3 perovskite light-absorbing layer, PEAI passivation layer, C 60 / BCP electron transport layer, silver electrode, P(DVB- g -V3D3- g -PFDA) encapsulation film, UV-curable adhesive, and cover glass.

[0116] To simulate the real situation of prolonged contact between the battery and the encapsulation material during actual operation as much as possible, the UVCA-coated device was placed in a nitrogen-filled glove box and left to stand for 7 days to allow the encapsulation material to fully wet the device surface, followed by impedance spectroscopy testing. Figure 23 The Nyquist curves of devices with different packaging schemes are shown in Tables 4 and 5. The electrochemical impedance spectroscopy (EIS) was fitted using an equivalent circuit, and the fitting results are listed in Tables 4 and 5. The results indicate that the charge transport resistance (CRT) of the device after UVCA packaging... R ct The series resistance (R0) increased significantly, from 742.8 Ω in the original state to 1422.9 Ω, indicating that the electron extraction process from the perovskite layer to the electron transport layer was hindered. In stark contrast, after depositing an iCVD polymer film on the device surface, the measured Nyquist curve almost completely overlapped with the curve of the original device, and the series resistance (R0) was significantly lower. s The basic structure remains unchanged. R ct The charge transfer resistance decreased only slightly from 966.8 Ω to 972.1 Ω, indicating that the effect of the iCVD deposition process on the charge transfer process is negligible. Further coating of UVCA on the iCVD film resulted in a charge transfer resistance of 1089.2 Ω after 7 days, an increase of only 122.4 Ω compared to the original device, far less than the 680.1 Ω increase in the control group. Electrochemical impedance spectroscopy (EIS) and conductivity results suggest that the iCVD wrinkled film can suppress the effect of UVCA on charge transfer, possibly by hindering UVCA penetration.

[0117] Table 4 Impedance spectral fitting data of devices using UVCA packaging

[0118] Table 5 Impedance spectral fitting data of devices using Target packages

[0119] To evaluate the impact of target packaging on the spectral response of the device, the EQE spectra of the unpackaged device and the target-packaged device were compared and analyzed. Figure 24 As shown, the EQE spectra of the device before and after packaging are almost identical, with no significant decrease in the 300–850 nm wavelength range. The integrated current density remains essentially unchanged, at 23.49 mA / cm² before packaging. 2 After packaging, it has an A / cm² value of 23.42. 2 EQE results indicate that the Target package does not significantly impair the light absorption of the device.

[0120] The above experiments demonstrate that Target encapsulation with iCVD wrinkled film provides better protection for perovskite films than UVCA encapsulation alone. To further investigate the role of Target encapsulation in the stability of perovskite solar cells, this study placed the encapsulated devices in a constant temperature and humidity chamber maintained at 25 ℃ and 65% relative humidity for aging tests. The devices were tested at regular intervals. JV A curve was generated to monitor the aging of the device. The measured data was normalized, and the results are as follows: Figure 25 As shown, the efficiency of unencapsulated devices rapidly declines during aging, exhibiting a clear degradation trend. After 48 hours of aging, the PCE (Power Consumption Equation) only maintains 75% of the initial efficiency, and after 552 hours, the PCE further degrades to 29% of the initial efficiency. This is attributed to the erosion of perovskite by moisture, leading to a rapid decline in device performance. Conversely, devices using Target encapsulation exhibit excellent humidity stability, maintaining 80% of their initial efficiency even after 1350 hours of continuous aging under high humidity conditions. Thanks to the excellent hydrophobic properties of the iCVD wrinkled film and its hermetically sealed packaging, Target encapsulation effectively resists the intrusion of external moisture, significantly improving the long-term stability of perovskite solar cells in high humidity environments.

[0121] Subsequently, maximum power point (MPP) tracking tests were conducted in an air environment of 25 °C and ~30% RH to evaluate the operational stability of the device. The light source used for the tests was an LED with an equivalent luminous intensity of 1 sun. The normalized PCE variation results are as follows: Figure 26 As shown, the efficiency of the unpackaged raw device decays rapidly, reaching less than 40% of the initial PCE after 100 hours, indicating poor intrinsic stability. The Target-packaged device exhibits excellent operational stability, maintaining 70% of its initial efficiency after 500 hours of continuous operation, demonstrating that Target packaging improves device operational stability.

[0122] This application utilizes the low-temperature, solvent-free advantage of iCVD technology to convert P(DVB- g -V3D3- g -PFDA) wrinkled thin films were deposited on the silver electrode surface of perovskite solar cells to achieve preliminary device encapsulation. The protective effect of the wrinkled films was first tested. Immersion test results showed that the iCVD wrinkled films effectively blocked water molecules from contacting the perovskite active layer, significantly delaying the degradation of the perovskite film in water. PL spectroscopy and JV The curves are basically consistent before and after iCVD coating. After encapsulation, the device maintains 98.1% of the initial efficiency, proving that the iCVD deposition process does not cause significant damage to the photovoltaic performance of the device.

[0123] Subsequently, based on the iCVD wrinkled film, a Target encapsulation system was constructed by combining UV-curable adhesive and cover glass. An unencapsulated group and a UVCA-encapsulated group were set up as controls to explore the unique role of the iCVD wrinkled film in the encapsulation system. Heat aging test results showed that the Target encapsulation system provided significantly better protection for the perovskite film than simple UVCA encapsulation. The perovskite film encapsulated by Target maintained its original crystal structure after aging, exhibited the lowest degree of absorption spectrum decline, and almost no PbI2 production. Electrochemical impedance spectroscopy and conductivity tests confirmed that the iCVD wrinkled film can form a dense physical barrier layer, effectively alleviating the problems of increased charge transport resistance and hindered charge extraction caused by the infiltration of small molecules in the UV-curable adhesive, achieving compatibility with traditional UV-curable adhesive encapsulation. Furthermore, humidity stability test results showed that the device packaged by Target could still maintain 80% of its initial PCE after aging at 65% RH for 1350 h; in an air environment of 25 ℃ and ~30% RH, the efficiency of the maximum power point decreased by only 30% after 500 h of continuous operation under 1 sun light intensity, while the efficiency of the unpackaged device decreased by more than 60% within 100 h, which fully verified the excellent performance of the Target packaging system in improving the humidity stability and long-term operational stability of the device.

[0124] Overall, the excellent hydrophobic properties of the iCVD wrinkled film greatly resist perovskite degradation caused by moisture erosion, and the low-temperature, solvent-free deposition conditions of the iCVD process ensure that device performance is not compromised. The synergistic effect of the wrinkled film and UVCA not only further improves the encapsulation effect and enhances device stability, but also mitigates the charge extraction obstruction problem caused by UVCA penetration.

[0125] Therefore, the fifth objective of this application is to provide an application of iCVD micro-nano wrinkled film in perovskite photovoltaic devices, wherein the iCVD micro-nano wrinkled film is a P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film, and the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is used for light management or encapsulation of perovskite solar cells.

[0126] When the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is used for light management of perovskite solar cells, the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is disposed on the outer side of the ITO conductive glass to guide incident light to undergo multiple reflections on the wrinkled structure of the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film and form a refractive index gradient, thereby reducing the reflection loss on the light-incident side of the ITO conductive glass.

[0127] When the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is used for encapsulation of perovskite solar cells, the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is disposed on the side of the Ag electrode away from the perovskite photovoltaic functional layer, and together with the UV-curable adhesive and cover glass disposed on the side away from the Ag electrode, it forms a target encapsulation structure.

[0128] All articles and references disclosed above, including patent applications and publications, are incorporated herein by reference for various purposes. The term “substantially constitutes…” used to describe a combination should include the identified elements, components, parts, or steps, as well as other elements, components, parts, or steps that do not substantially affect the essential novelty of the combination. The use of the terms “comprising” or “including” to describe combinations of elements, components, parts, or steps herein also contemplates embodiments substantially constituted by such elements, components, parts, or steps. The use of the term “may” herein is intended to indicate that any described attribute included by “may” is optional.

[0129] Multiple elements, components, parts, or steps can be provided by a single integrated element, component, part, or step. Alternatively, a single integrated element, component, part, or step can be divided into multiple separate elements, components, parts, or steps. The use of "a" or "an" to describe an element, component, part, or step does not imply the exclusion of other elements, components, parts, or steps.

[0130] It should be understood that the above description is for illustrative purposes and not for limitation. Many embodiments and applications beyond the provided examples will be apparent to those skilled in the art upon reading the above description. Therefore, the scope of this teaching should not be determined by reference to the above description, but rather by reference to the foregoing claims and the full scope of their equivalents. For purposes of completeness, all articles and references, including disclosures in patent applications and publications, are incorporated herein by reference. The omission of any aspect of the subject matter disclosed herein in the foregoing claims is not intended as a waiver of that subject matter, nor should it be construed as an indication that the applicant has not considered that subject matter as part of the disclosed inventive subject matter.

Claims

1. A perovskite solar cell with an iCVD micro / nano wrinkled thin film, characterized in that, The invention includes an ITO conductive glass and a perovskite photovoltaic functional layer disposed on the conductive side of the ITO conductive glass. A P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film formed by initiation chemical vapor deposition is disposed on the outer side of the ITO conductive glass. The P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film includes a PDVB film deposited on the outer side of the glass and PV3D3 and PPFDA films formed on the PDVB film. The P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film has a micro-nano wrinkled structure facing the incident light side to guide the incident light to undergo multiple reflections on the micro-nano wrinkled structure and form a refractive index gradient.

2. The perovskite solar cell according to claim 1, characterized in that, The PDVB film is a dense polyvinylbenzene film; the PV3D3 film is a poly(2,4,6-trivinyl-2,4,6-trimethylcyclotrisiloxane) film; and the PPFDA film is a poly(1H,1H,2H,2H-perfluorodecyl acrylate) film.

3. The perovskite solar cell according to claim 1, characterized in that, The perovskite photovoltaic functional layer includes a NiOx thin film, a Me-4PACz layer, a FA0.85MA0.1Cs0.05PbI3 perovskite layer, a PEAI layer, a C60 layer, a BCP layer, and an Ag back electrode, which are sequentially disposed on the conductive side of the ITO conductive glass.

4. The perovskite solar cell according to claim 1, characterized in that, The thickness of the PDVB film is 20 nm - 1000 nm, the thickness of the PV3D3 film is 20 nm - 1000 nm, and the deposition time of PPFDA is 1 min - 1 h.

5. A method for preparing a perovskite solar cell with an iCVD micro / nano-wrinkled thin film as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Fabrication of perovskite solar cells with ITO conductive glass and perovskite photovoltaic functional layers; Wipe the outer surface of the ITO conductive glass clean; Place the ITO conductive glass face up into the initiation chemical vapor deposition reaction chamber; A PDVB film is deposited on the outer side of the glass. PV3D3 and PPFDA were synthesized to obtain P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled films.

6. A perovskite solar cell with an iCVD micro / nano wrinkled thin film, comprising an ITO conductive glass, a perovskite photovoltaic functional layer disposed on the ITO conductive glass, and an Ag electrode, characterized in that, A P(DVB-g-V3D3-g-PFDA) encapsulation film formed by initiation chemical vapor deposition is disposed on the side of the Ag electrode opposite to the perovskite photovoltaic functional layer. A UV-curable adhesive is disposed on the side of the P(DVB-g-V3D3-g-PFDA) encapsulation film opposite to the Ag electrode. A cover glass is disposed on the side of the UV-curable adhesive opposite to the P(DVB-g-V3D3-g-PFDA) encapsulation film.

7. The perovskite solar cell according to claim 6, characterized in that, The P(DVB-g-V3D3-g-PFDA) encapsulation film is grown on the surface of the Ag electrode; the surface of the P(DVB-g-V3D3-g-PFDA) encapsulation film has a wrinkled structure. Preferably, the PDVB film thickness is 100nm-20μm, and the PV3D3 film thickness is 100nm-20μm; The deposition time for PPFDA is 1 min to 5 h.

8. The perovskite solar cell according to claim 6, characterized in that, The perovskite solar cell, from the direction of incident light, comprises, in sequence, ITO conductive glass, NiOx hole transport layer, Me-4PACz self-assembled layer, FA0.85MA0.1Cs0.05PbI3 perovskite light-absorbing layer, PEAI passivation layer, C60 / BCP electron transport layer, silver electrode, P(DVB-g-V3D3-g-PFDA) encapsulation film, UV-curable adhesive, and cover glass.

9. A method for encapsulating a perovskite solar cell with an iCVD micro / nano wrinkled thin film as described in any one of claims 6 to 8, characterized in that, Includes the following steps: After vapor deposition of C60 and BCP, the sample is removed from the vapor deposition machine, the functional layers around the sample are scraped off, and the functional layers in the middle are left to cover ITO. The sample was placed in a vapor deposition machine for Ag electrode deposition. The prepared device is placed in the initiation chemical vapor deposition reaction chamber with the Ag electrode facing upward, and a P(DVB-g-V3D3-g-PFDA) encapsulation film is formed on the surface of the Ag electrode. UV-curable adhesive is added to the surface of the P(DVB-g-V3D3-g-PFDA) encapsulation film, a cover glass is placed on top, and pressure is applied to cover the perovskite with the UV-curable adhesive. The UV-curable adhesive is solidified by irradiation under a UV lamp to obtain the Target encapsulation structure.

10. An application of iCVD micro / nano-wrinkled thin films in perovskite photovoltaic devices, characterized in that, The iCVD micro-nano wrinkled film is a P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film, which is used for light management or encapsulation of perovskite solar cells. When the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is used for light management of perovskite solar cells, the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is disposed on the outer side of the ITO conductive glass to guide incident light to undergo multiple reflections on the wrinkled structure of the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film and form a refractive index gradient. When the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is used for encapsulation of perovskite solar cells, the P(DVB-g-V3D3-g-PFDA) micro-nano wrinkled film is disposed on the side of the Ag electrode away from the perovskite photovoltaic functional layer, and together with the UV-curable adhesive and cover glass disposed on the side away from the Ag electrode, it forms a target encapsulation structure.